Kawalan Kesejahteraan Psikologi Berasaskan Konsep Psikospiritual dalam Al-Quran: Suatu Analisis: Psychological Well-Being Control Based On Psychospiritual Concepts In The Quran: An Analysis - Kamarul Zaman, Rahim; Nasir, Khairulnazrin; Muhammad Saleh, Mujiburrahman; Ab Hamid, Nur Shahidah (‘Abqari Journal, 2022)
The value of psychological well-being is an important post-pandemic discourse of covid-19. The impact of this pandemic caused the psychological well-being index of Malaysians at a moderate level with an overall score of 7.2. In this regard, various initiatives at the global level to control the sustainability of psychological well-being through psychospiritual approaches are actively pursued by various parties. Among them are Mindfulness Meditation, Ayurveda, Yoga and other non-Muslim psychospiritual approaches. Thus, the purpose of this study is to analyse the concept of psychospiritual in the Qur'an as a control mechanism for psychological well-being. Based on a qualitative method with a thematic content analysis approach, this study found that the concept of psychospiritual in the Quran is holistic. The concepts of iṭmi’nān al-qulūb (peace of mind) and al-Sakīnah (tranquillity) which are discussed twenty times in the Qur’an are part of the core underlying the Qur’an-based psychospiritual approach. A combination of understanding about it is found to be able to control and stabilise the mind or emotions. In conclusion, the concept of psychospiritual in the Qur’an is significant and deserves to be dignified as part of the complementary mechanism of psychological well-being control. ABSTRAK Nilai kesejahteraan psikologi merupakan wacana penting pasca pandemik covid-19. Kualiti dan kelestarian kesejahteraan psikologi merupakan sesuatu yang bersifat subjektif dan berbeza antara setiap individu. Impak pandemik ini menyaksikan indeks kesejahteraan psikologi rakyat Malaysia berada pada tahap sederhana dengan skor keseluruhan 7.2. Sehubungan dengan itu, inisiatif bagi mengawal kelestarian kesejahteraan psikologi giat diusahakan pelbagai pihak. Kualiti emosi, kepuasan hidup, kefungsian psikologi dan keupayaan berinteraksi dengan persekitaran merupakan sebahagian indikator utama tahap kesejahteraan psikologi. Justeru, tujuan kajian ini dijalankan adalah bagi menganalisis konsep psikospiritual dalam al-Quran sebagai mekanisme kawalan kesejahteraan psikologi. Kajian berbentuk aplikasi teori ini, digarap berasaskan metode kualitatif dengan menggunakan pendekatan analisis kandungan secara tematik. Hasil kajian mendapati konsep psikospiritual dalam al-Quran adalah bersifat holistik. Konsep iṭmi’nān al-qulūb dan al-Sakīnah merupakan sebahagian teras yang mendasari pendekatan psikospiritual berasaskan al-Quran. Kombinasi kefahaman mengenainya didapati mampu mengawal dan menstabilkan fikiran atau emosi. Kesimpulannya, konsep psikospiritual dalam al-Quran adalah signifikan dan wajar dimartabatkan sebagai sebahagian mekanisme komplementari kawalan kesejahteraan psikologi.